Sex pheromone of Lonomia obliqua: daily rhythm of production, identification, and synthesis - Lima, Eraldo R.; Zarbin, Paulo H. G.; Lorini, Lisete M.; Ambrogi, Bianca G.; Vidal, Diogo M. (Journal of Chemical Ecology, 2007)
The sex pheromone of Lonomia obliqua Walker (Lepidoptera: Saturniidae) was studied in the laboratory. All female calling occurred during the scotophase. Most females (70.6%) called first within 24 hr of eclosion. Calling varied with age of female, with older (5- to 6-day-old) females calling earlier in the scotophase and for longer durations than younger (0- to 1-day-old) females. The sex pheromone gland of 1- to 3-day-old virgin females was extracted during the calling peak. A Y-olfactometer bioassay showed significant attraction of males to a filter paper containing the female gland extract. Gas chromatographic-electroantennogram detection (GC-EAD) analysis of the extract indicated the presence of at least two possible pheromone components. Gas chromatographic-mass spectrometric analysis of the major GC-EAD-active peak indicated a hexadecenyl acetate; chemical derivatization indicated Δ11 unsaturation. Synthetic samples of (E)- and (Z)-11-hexadecenyl acetate were obtained by coupling 10-bromo-1-decanol and 1-hexyne, utilizing lithium chemistry. The comparison of the retention time of dimethyl disulfide derivatives of the natural compound, to those of synthetic chemicals, confirmed the natural compound as (E)-11-hexadecenyl acetate. The minor component was identified as the related alcohol, (E)-11-hexadecenol. The ratio of the two components in female extract was 100:35. Preliminary tests of males in a Y-olfactometer showed that their response to a mixture of the two compounds was not significantly different from that to gland extract.
Keywords: Hemorrhagic caterpillar; Sex pheromone; (E)-11-Hexadecenyl acetate; (E)-11-Hexadecenol; Calling behavior